Overview of Q fever in Brazil: an underestimated zoonosis - de França, Danilo Alves [UNESP]; Mioni, Mateus de Souza Ribeiro [UNESP]; Fernandes, Jorlan; de Lemos, Elba Regina Sampaio; Duré, Ana Íris de Lima; Silva, Marcos Vinicius Ferreira; Langoni, Helio [UNESP]; Megid, Jane [UNESP] (FapUNIFESP (SciELO), 2023)
This review aims to provide current information about Q fever, elucidating the etiological, epidemiological, pathogenic, clinical, diagnostic, therapeutic, and prophylactic aspects of the disease for the medical community. We discuss the main forms of presentation of the agent, its ability to persist in the body, the infinite possibilities of susceptible hosts, the main known forms of transmission, its importance in populations at occupational risk, and the role of arthropods in the natural history of the disease. Focusing on Brazil, we present the cases already described and studies developed since its first report, and how there is still much to unravel. We are aware of the possibilities of the persistence of the agent and the development of severe clinical pictures and the specific treatments currently instituted. We also wish to raise awareness about the future, the new genotypes that are emerging, the need to study the effects of vaccines, and the impact of Q fever on the population. Q fever is a poorly understood disease in Latin America, and recent studies, especially in Brazil, have revealed the importance of developing new studies.
Keywords: Coxiella burnetii; Emerging diseases; Q fever; Zoonosis